Dpal-ldan Bla-ma Dam-pa ʼKhrul-źig Rin-po-che Ṅag-dbaṅ-tshe-riṅ gi rnam thar kun tu bzaṅ poʼi zlos gar yid kyi bcud len : the life and songs of esoteric realization of Grub-chen Ṅag-dbaṅ-tshe-riṅ - Ṅag-dbaṅ-tshe-riṅ, ʼKhrul-źig, 1717-1794 (Tobdan Tsering, 1978)
Life and works of a religious leader of the Drukpa Kargyudpa sect from Zangskar in Ladakh.